Explicating explicit reflection in nature of science education: a systematic literature review - Boven, Lotte; De Schrijver, Jelle; Pinxten, Rianne; Van Petegem, Peter (Frontiers in Education, 2025)
For over two decades, “explicit reflection” has been a cornerstone concept in Nature of Science education. Many studies underscore the crucial role of Explicit Reflection in effective Nature of Science education, yet its ubiquity is accompanied by ambiguity in its definition and application. In this study, the aim is to comprehensively map the evolving meanings of Explicit Reflection in Nature of Science education. Conducting a systematic review, articles providing definitions for Explicit Reflection in Nature of Science education between 2000 and 2023, were examined following PRISMA guidelines. 61 definitions that adhered to our predefined criteria were systematically identified and selected. Subsequently, a data analysis process was conducted involving both discourse analysis and thematic synthesis. Using discourse analysis, both persistent themes and evolving patterns were identified, shedding light on the dynamic character of Explicit Reflection within the context of Nature of Science education. In parallel, during the thematic synthesis, a taxonomy of 25 descriptive themes was developed and further distilled into four analytical categories. These four key analytical themes encompass: “the meaning of explicit”, “the meaning of reflection”, “learning environment” and “cognitive process dimensions”. Two types of Explicit Reflection: the student-centered and teacher-centered types, were constructed. From these, student-centered definitions of Explicit Reflection incorporate higher cognitive process dimensions and offer a more comprehensive definition. In conclusion, this study clarifies the multifaceted nature of Explicit Reflection in Nature of Science education, providing a nuanced framework that distinguishes between student-centered and teacher-centered approaches. By offering a detailed taxonomy and highlighting the cognitive depth of student-centered definitions, this work lays the groundwork for more precise implementation and future research in Nature of Science pedagogy.